2007
DOI: 10.1111/j.1440-169x.2007.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of two M type mitochondrial DNA from sperm and unfertilized eggs to offspring in Mytilus galloprovincialis

Abstract: In Mytilus mussels, paternal mitochondrial DNA (mtDNA) from sperm is known to be transmitted to offspring. This phenomenon is called doubly uniparental inheritance (DUI). Under DUI, sperm mtDNA (M type) is inherited only by males. Female mussels receive maternal mtDNA (F type). However, in our previous study, we showed female and unfertilized eggs have both F and M types. We hypothesized that the two M types both from sperm and unfertilized eggs were transmitted to offspring. To test the hypothesis, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Under DUI, female bivalves transmit their mitochondria (carrying F mtDNA) to both sons and daughters, as in SMI, but males pass on their mitochondria (via sperm carrying M mtDNA) to only sons (e.g., [11] but see [12]). At the organismal level, male bivalves with DUI are thus heteroplasmic and contain both M and F genomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under DUI, female bivalves transmit their mitochondria (carrying F mtDNA) to both sons and daughters, as in SMI, but males pass on their mitochondria (via sperm carrying M mtDNA) to only sons (e.g., [11] but see [12]). At the organismal level, male bivalves with DUI are thus heteroplasmic and contain both M and F genomes.…”
Section: Introductionmentioning
confidence: 99%
“…In male somatic tissues, the F genome predominates while in male gonadal tissues, the M genome is predominant [13] and it appears to be the exclusive type in sperm [14]. In females, both somatic and gonadal tissues typically contain the F genome, but the occasional presence of a small amount of the M genome has been demonstrated in somatic tissues and ovaries of some species [12-16]. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DUI is a “mother-to-daughter” and “father-to-son” mtDNA inheritance system where females transmit their mt genomes (F mtDNA) to both sons and daughters, and males transmit their mt genomes (M mtDNA) to their sons [20][23]. Female offspring are typically homoplasmic ( = containing one mt genome) and male offspring are heteroplasmic [21], [23] but see [24], [25]. In marine mussels Mytilus spp., male somatic tissue contains predominantly the mtDNA of the mother (F genome) but male gametes contain exclusively the mtDNA of the father (M genome) [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the inference that these individuals are derived from heteroplasmic eggs indicates that the failure to exclude paternal mtDNA by female embryos does not just lead to the inclusion of M haplotypes into the soma but, at least occasionally, into the germ line as well. Obata et al (2006Obata et al ( , 2007 and Sano et al (2007) have both previously shown heteroplasmic (the presence of both F and M haplotypes) unfertilized Mytilus galloprovincialis-spawned eggs. When fertilizing heteroplasmic eggs in the laboratory, Obata et al (2007) found that the M haplotype in the resulting progeny was consistent with the M type of the sperm.…”
Section: Discussionmentioning
confidence: 97%
“…Obata et al (2006Obata et al ( , 2007 and Sano et al (2007) have both previously shown heteroplasmic (the presence of both F and M haplotypes) unfertilized Mytilus galloprovincialis-spawned eggs. When fertilizing heteroplasmic eggs in the laboratory, Obata et al (2007) found that the M haplotype in the resulting progeny was consistent with the M type of the sperm. They also found 30% (n = 6) of the adult mussels that they used contained 2 M haplotypes and an F haplotype ).…”
Section: Discussionmentioning
confidence: 97%